The honeybee (Apis mellifera) developmental state shapes the genetic composition of the deformed wing virus-A quasispecies during serial transmission - Yañez, Orlando (Sci Rep, 2020)
The main biological threat to the western honeybee (Apis mellifera) is the parasitic mite Varroa destructor, largely because it vectors lethal epidemics of honeybee viruses that, in the absence of this mite, are relatively innocuous. The severe pathology is a direct consequence of excessive virus titres caused by this novel transmission route. However, little is known about how the virus adapts genetically during transmission and whether this influences the pathology. Here, we show that upon injection into honeybee pupae, the deformed wing virus type-A (DWV-A) quasispecies undergoes a rapid, extensive expansion of its sequence space, followed by strong negative selection towards a uniform, common shape by the time the pupae have completed their development, with no difference between symptomatic and asymptomatic adults in either DWV titre or genetic composition. This suggests that the physiological and molecular environment during pupal development has a strong, conservative influence on shaping the DWV-A quasispecies in emerging adults. There was furthermore no evidence of any progressive adaptation of the DWV-A quasispecies to serial intra-abdominal injection, simulating mite transmission, despite the generation of ample variation immediately following each transmission, suggesting that the virus either had already adapted to transmission by injection, or was unaffected by it.